2015
DOI: 10.1038/srep13820
|View full text |Cite
|
Sign up to set email alerts
|

Thermal post-treatment alters nutrient release from a controlled-release fertilizer coated with a waterborne polymer

Abstract: Controlled-release fertilizers (CRF) use a controlled-release technology to enhance the nutrient use efficiency of crops. Many factors affect the release of nutrients from the waterborne polymer-coated CRF, but the effects of thermal post-treatments remain unclear. In this study, a waterborne polyacrylate-coated CRF was post-treated at different temperatures (30 °C, 60 °C, and 80 °C) and durations (2, 4, 8, 12, and 24 h) after being developed in the Wurster fluidized bed. To characterize the polyacrylate membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…These detailed data were obtained under sufficient water conditions, which indicated that the retaining ability of water was marginal, and that consequently, the improved crop production can be ascribed to the fact that BSRFs could effectively control the loss of fertilizer nutrients and thus improve the retaining ability of nutrients, which enable BSRFs to continuously supply sufficient fertilizer nutrients for the growth of cotton, and thus contribute to cotton growth. 1,36 Furthermore, BC embedded into BSRFs can create favorable habitats for soil microorganisms, while also providing some other nutrients for plants, all of which was conducive to cotton plant growth. Furthermore, total N-use efficiencies of the cotton plants fertilized with NH 4 Cl, N-BC, and BSRFs were 35.75%, 49.17%, and 64.27%, respectively.…”
Section: Acs Sustainable Chemistry and Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…These detailed data were obtained under sufficient water conditions, which indicated that the retaining ability of water was marginal, and that consequently, the improved crop production can be ascribed to the fact that BSRFs could effectively control the loss of fertilizer nutrients and thus improve the retaining ability of nutrients, which enable BSRFs to continuously supply sufficient fertilizer nutrients for the growth of cotton, and thus contribute to cotton growth. 1,36 Furthermore, BC embedded into BSRFs can create favorable habitats for soil microorganisms, while also providing some other nutrients for plants, all of which was conducive to cotton plant growth. Furthermore, total N-use efficiencies of the cotton plants fertilized with NH 4 Cl, N-BC, and BSRFs were 35.75%, 49.17%, and 64.27%, respectively.…”
Section: Acs Sustainable Chemistry and Engineeringmentioning
confidence: 99%
“…Fertilizers are the fundamental factor for agriculture production both in quality and quantity. With an increasing world population and diminishing arable land, it is necessary to employ larger quantities of chemical fertilizers, especially nitrogen (N), phosphorus (P), and potassium (K), to meet the global food demands. N is the most widely applied nutrient for good soil fertility and plant growth, although the utilization efficiency is only about 30–40% . High N losses via ammonia volatilization, nitrate leaching, and nitrous oxide emissions lead to a low efficiency, large economic losses, and adverse environmental impacts, while also constraining sustainable agricultural development. ,, The use of slow-release fertilizers (SRFs) is a promising strategy which can simultaneously improve N utilization efficiency and reduce environmental impact.…”
Section: Introductionmentioning
confidence: 99%
“… 30 The N-release profile (biochar nitrogen fertilizer (BNF-2), biobased biochar nitrogen fertilizer (BBNF), and BCRNF) following a parabolic diffusion model indicates that the release involves a combination of dissolution, adsorption, and diffusion processes. 31 As revealed from SEM based microstructure analysis of biochar+urea (B+U), postnutrient release in water results in a smooth and strongly networked surface morphology with microholes ( Figure 4 a). However, an undulating and coarse surface was evident for BCRNF including nanoscale rough bulges ( Figure 4 b).…”
Section: Controlled Release Mechanism Of Nutrientsmentioning
confidence: 99%
“…Applications of nanotechnology as a plant nutritional mediator in the form of modern nanofertilisers are referred to as controlled release fertilisers (CRFs). CRFs designed for controlling nutrient release behaviours that rely on thermal post‐treatment parameters, can enhance the nutrient use efficiency of crops . Yet, soil temperature‐dependent CRFs need to be comprehensively monitored with different crops to obtain reliable data regarding release characteristics and duration of nutrient release.…”
Section: Nanotechnology‐based Opportunities In Fertilisersmentioning
confidence: 99%
“…CRFs designed for controlling nutrient release behaviours that rely on thermal post-treatment parameters, can enhance the nutrient use efficiency of crops. 186 Yet, soil temperature-dependent CRFs need to be comprehensively monitored with different crops to obtain reliable data regarding release characteristics and duration of nutrient release. An increase in temperature, from 20 to 40 ∘ C, was shown to differentially increase the rate of release of various nutrients from a polymer-coated CRF, such that nitrogen release into the water was rapid in comparison to potassium, whereas phosphate was significantly slower.…”
Section: Nanotechnology-based Opportunities In Fertilisersmentioning
confidence: 99%